Pengembangan Media Pembelajaran Google Sites: Validitas, Kepraktisan, dan Efektivitas pada Instalasi Tenaga Listrik SMK - Muhammad Oksa Pratama Putra; Fendi Achmad; Puput Wanarti Rusimamto; Ali Nur Fathoni (Educational Journal, 2026)
The utilization of information technology in vocational education still faces persistent challenges, namely the dominance of lecture methods and conventional presentation media that inadequately support students' understanding of abstract technical installation materials, particularly in the Electrical Power Installation element at SMK Negeri 7 Surabaya. This study aimed to develop an interactive learning medium based on Google Sites and to examine its validity, practicality, and effectiveness on student learning outcomes. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involving 37 eleventh-grade students majoring in Electrical Power Installation Engineering as the trial subjects. Data were collected through media and material expert validation sheets, student response questionnaires, and learning outcome tests (pre-test and post-test), then analyzed using Aiken's V index, practicality percentage, and the N-gain test. The results showed media and material validity scores of 0.85 and 0.87 respectively (average 0.86, high category), a practicality level of 89.92% (very practical category), and an improvement in learning outcomes from an average pre-test score of 62 to 88.19 in the post-test, with an N-gain score of 0.7488 (74.88%, high category). The Google Sites-based learning medium was proven valid, practical, and effective for use in electrical power installation instruction at the vocational school level.